Acquired von Willebrand's syndrome with IgM inhibitor against von Willebrand's factor. Issue 10 (October 1979) - Gouault-Heilmann, M; Dumont, M D; Intrator, L; Chenal, C; Lejonc, J L
Abstract : This report describes a patient without evident underlying disease, in whom an acquired von Willebrand's syndrome was discovered before surgery. Coagulation abnormalities included a borderline bleeding time, a low retention of platelets on glass beads, decreased levels of factor VIII procoagulant activity (VIIIAHF), factor VIII-related antigen (VIIIAg), and ristocetin-induced agglutination cofactor (VIIIVWF). After cryoprecipitate infusion the patient did not have the expected rise and there was no secondary increment in VIIIAHF. The patient was treated with prednisone for three weeks without significant improvement in the laboratory findings. Spontaneous resolution was observed long after this therapy. The haemostatic abnormalities were attributable to the presence of an inhibitor directed against VIIIVWF. The inhibitor was found in the IgM fraction. Its autoimmune nature is probable although we failed to demonstrate any inhibitory effect of Fab obtained from the patient's purified IgM. Despite the lack of inhibitory effect against VIIIAHF and VIIIAg, the low levels of all three activities of the factor VIII complex could be explained by the short half-life of immune complexes between factor VIII and the inhibitor.